How Are New Zealand Job Advertisements Perceived by Graduate Students From Mainland China: A Case Study - Cai, Lu (Auckland University of Technology, 2020)
The purposes of this study were (a) to explore how New Zealand job advertisements are perceived by graduate students from Mainland China, and (b) to identify if there are any potential areas for intercultural (mis)understanding. Since no studies have been published which have focused on this exact topic, this study will address a gap in the literature. The research design involved a qualitative approach, which consisted of interviews with participants, critical discourse analysis (CDA) of the job advertisements and intercultural discourse analysis. Interviews were used to collect descriptive data on how the postgraduate students ‘receive’ and ‘perceive’ the criteria the employer wants potential applicants to meet. The findings revealed that the Mandarin Chinese participants often found some of the terms used in the New Zealand advertisements quite ambiguous. They did not quite know what to make of those terms: they did not resonate with them. This increased their feelings of uncertainty as to what was expected of them and may have impacted their willingness to apply for the jobs advertised. The study also revealed that some of the lexical words and modal words obviously reflected what is required of applicants when they want to apply for the jobs. The design also included a comparative analysis of New Zealand and Mandarin Chinese job advertisements. Results indicated that people from different cultural backgrounds perceived similar or identical wording differently. Chinese applicants may misunderstand the covert meaning of New Zealand advertisements, and vice versa. Such points of difference affected the understanding of my participants who want to try a find a job in New Zealand. If they lack familiarity with intercultural and crosslinguistic differences, this may be reflected in the way they write their application and they may either not be selected for the interview, or not be able to do well in the interview. For future research, expanding the sample to a large group to look at how students ‘read’ and ‘perceive’ Chinese advertisements is suggested. It would be very useful to have some workshops specifically aimed at international students graduating from postgraduate courses and applying for jobs in New Zealand. If these students were “on the same page” as the employers and got the underlying, hidden meaning, they would definitely find it easier to succeed in an interview.
Keywords: Intercultural analysis; Comparative analysis of New Zealand and Mandarin Chinese job advertisements; Critical discourse analysis; Intercultural misunderstanding; Hofstede's cultural dimensions; Reception studies; High context culture; Low context culture